PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT PENGGUNAAN KOLAGEN INJEKSI DI INDONESIA - Abdul Ghofur; Siti Afiyah; Sholihan Sholihan (Universitas Islam Darul Ulum, 2017)
Consumer protection in Indonesia is considered to be of little concern, one example of the use of collagen injections which can be dangerous for patients who inject collagen not only makes the body fresh and healthy, but also makes the skin of the wearer smoother. More than that, this product is also claimed to make the wearer stay young. Excessive advertising, word of mouth, makes many women tempted to try. Moreover, in terms of relative prices, it is much cheaper than performing operations. The method used in this research is the normative juridical research type. Regulations related to the production and distribution of drugs and / or cosmetics in Indonesia, especially collagen injection, are contained in Law Number 8 of 1999 concerning Consumer Protection, Regulation of the Minister of Health Number 1010 / Menkes / Per / XI / 2008 concerning Drug Registration. Regulation of the Head of the Agency Number HK.04.1.33.12.11.09938 of 2011 concerning Criteria and Procedures for Withdrawal of Drugs Not Fulfilling Standards and / or Requirements and Law Number 36 Year 2009 concerning Health. In the Regulation of the Head of Drug and Food Control of the Republic of Indonesia Number 28 of 2013 concerning Supervision of the Importation of Medicinal Ingredients, Traditional Medicinal Materials, Health Supplement Ingredients and Food Ingredients into the Indonesian Territory the administrative responsibility The responsibility of business actors for the use of injectable collagen consists of criminal responsibility and civil liability.